The Discourse Analysis of Lucifer Morningstar’s Speech: Pragmatic and Stylistic Features - Jannatul Ferdous Himika; Fatema Akter (CV Projurnal Mitra Publikasi, 2025)
This study examines the pragmatic and stylistic dimensions of Lucifer Morningstar’s speech in the television series Lucifer (2016-2021). Drawing on Grice’s Cooperative Principle, Speech Act Theory, Politeness Theory, and stylistic frameworks proposed by Bednarek (2010) and Richardson (2010), the analysis investigates how maxim flouting, indirect speech acts, face negotiation, and rhetorical patterning function as mechanisms of identity construction and moral negotiation in fictional dialogue. The study employs a qualitative, descriptive discourse analysis of selected dialogues drawn from all six seasons, based exclusively on existing episode content and publicly available secondary sources. Findings demonstrate that Lucifer’s discourse exemplifies a sophisticated and simultaneous interplay of pragmatic deviation and stylistic embellishment, producing a character identity that is charismatic, morally ambiguous, and psychologically complex. These results contribute to existing scholarship on fictional discourse by offering an integrated analytical framework that addresses a persistent gap in the literature, wherein pragmatic and stylistic dimensions have largely been examined in isolation rather than in conjunction.